Karakteristik Fisikokimia dan Sensori Mayonnaise pada Berbagai Komposisi Asam Lemak dari Penggunaan Minyak Nabati Berbeda - Hanifah Nuryani Lioe; Nuri Andarwulan; Dwi Rahmawati (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Mayonnaise is an oil in water emulsion and used as condiment. Different vegetable oils used for mayonnaise production give different fatty acid compositions. The objective of this study was to determine physicochemical and sensory properties of mayonnaise in the use of different vegetable oils, by analyzing pH, color and viscosity as well as aroma and taste profiles by quantitative descriptive analysis. Sesame oil, palm oil, coconut oil, soybean oil, sunflower oil, a mixture (1:1)of coconut oil and sunflower oil or palm oil and soybean oil were used in formulations to give different compositions of polyunsaturated fatty acids (PUFA), monounsaturated fatty acids (MUFA) and saturated fatty acids (SFA). Mayonnaise characteristics including pH, color (L) and viscosity values which were ranged at 3.12–3.87, 87.47–89.58 and 3700–5513 cp respectively, were less associated to different fatty acid compositions. This also happened to sensory profiles. However principal component analysis result could map SFA/MUFA/PUFA with different characteristics of mayonnaise color, aroma and taste. Mayonnaise samples which correlated to PUFA had lighter color, and characteristics of oily taste and oil aroma, with the use of sunflower oil, meanwhile samples of soybean oil which also correlated to PUFA had the characteristics of mustard aroma, savory taste, acid taste, eggy aroma and mustard taste. MUFA correlated to sweet taste. Characteristics of lemon aroma was close to SFA with the use of coconut oil or its mixture. Therefore, color, aroma and taste of mayonnaise can be affected by the use of different fatty acid compositions.